Formulasi dan karakterisasi biodegradable film berbahan chitosan dan sodium alginate dengan kombinasi pati ganyong dan konjak glukomanan - David Rusliman; Rumpoko Wicaksono; Condro Wibowo (AGROINTEK, 2025)
Biodegradable film is an alternative way to reduce conventional plastic based on petroleum, which is difficult to degrade and can cause severe environmental pollution. Biodegradable films based on chitosan, sodium alginate, sodium alginate combined with canna starch and konjac glucomannan were investigated in this research. This research aims to determine the mechanical characteristics and optimum of different polymer types and the plasticizer concentration added to the biodegradable film solution. This research was done in a completely randomized design on twelve treatment combinations. The total formulation used for each type of polymer is 2% (w/v), and the concentration of sorbitol is 1% (v/v), 1,5% (v/v), and 2% (v/v). The average thickness of this research is 0,15 – 0,20 mm, the average moisture content value for each treatment ranges from 18% - 30%, the elongation value ranges from 11,75 – 59,94%, the tensile strength value ranges from 0,033 – 0,277 MPa and Water Vapor Transpiration Rate value (WVTR) range from 2,65 – 5,91 (g/m2.hour). The mechanical characteristics of food packaging materils are based on the value of elongation, WVTR, and tensile strength. Code P4S2 has the applicable value of elongation, WVTR, and tensile strength, with an elongation value of 51.75%, WVTR of 3.36 (g/m2.hour) and tensile strength of 0,05 MPa.